Review: Migration and New Media: Transnational Families and Polymedia (Mirca Madianou and Daniel Miller) - Becky Faith (tripleC: Communication, Capitalism & Critique, 2012)
Review of Migration and New Media: Transnational Families and Polymedia (Mirca Madianou and Daniel Miller)